Advance Optical Properties and Emerging Applications of 2D Materials - Kumbhakar, Partha; Chowde Gowda, Chinmayee; Tiwary, Chandra Sekhar (Frontiers in Materials, 2021)
Last several decades, a great effort has been devoted to two dimensional (2D) materials on account of their optical properties that have numerous applications in the optoelectronic world in the range of light-emitting diodes, optical sensors, solar energy conversion, photo-electrochemical cells, photovoltaic solar cells, and even in the bio-medical sector. First we have provided an outline of linear optical properties of 2D materials such as graphene, TMDs, h-BN, MXenes, perovskite oxide, and metal-organic framework. Then we discuss the optoelectronic properties of the 2D materials. Along with these, we also highlight the important efforts in developing 2D optical materials with intensive emission property at a broad wavelength from ultraviolet to near-infrared. The origin of this tuneable emission has been discussed decoratively. Thickness and layer-dependent optical properties have been highlighted and are explained through surface defects, strain, vacancy, doping, and dangling bonds emerging due to structural change in the material. The linear and nonlinear optical properties in 2D MXene and perovskite oxides are also impressive due to their potential applications for next-generation devices with excellent optical sensitivity. Finally, technological innovations, challenges, and possible tuning of defects and imperfections in the 2D lattice are discussed.